Web-Based Healthcare Service System Development Using RAD Method for Community Health Center Efficiency Improvement - Nathanael Eliasher Iroth; Chriestie Ellyane Juliet Clara Montolalu; Mahardika Inra Takaendengan; Yohanes Andreas Robert Langi; Wisard Widsli Kalengkongan; Dodisutarma Lapihu (Universitas Teknokrat Indonesia, 2026)
This research aims to design and develop a healthcare service website for Puskesmas Modoinding to improve efficiency and accessibility of public health services. Previously, information delivery including doctor schedules, service types, operating hours, and patient registration was conducted manually, often causing delays and limited information distribution. The system was developed using the Rapid Application Development (RAD) method, comprising four phases: requirements planning, system design, development, and implementation. Data collection employed interviews, observation, and literature study with 12 stakeholders (10 patients, 2 administrators). The website was built using HTML, CSS, JavaScript, PHP, and MySQL database. Black Box Testing demonstrated 100% success rate across 28 test scenarios covering admin and patient interfaces. System Usability Scale (SUS) evaluation yielded average scores of 85.5 for patients and 87.5 for administrators, both exceeding the 'Very Good' threshold of 80. Ten core features were successfully implemented including online registration, queue status checking, and administrative data management. The developed website enables community members to access healthcare information remotely without physical visits, reducing average registration time by approximately 40%. This research concludes that web-based healthcare systems using RAD methodology can significantly improve service efficiency at community health centers while meeting user requirements and usability standards.